(untitled) (Global Journal of Human-Social Science, 2021)
Without language, we cannot imagine our society. The English language acts as a spinal cord in our modern India though English is a second language. Indians face many obstacles to teach English as a second language on Indian soil. This paper tries to capture the problems in its limited way, and accept the English language as a gift.